PERMAINAN FINGER PAINTING UNTUK PENGEMBANGAN KEMAMPUAN MOTORIK HALUS ANAK USIA DINI - Maria Evivani; Renti Oktaria (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2020)
This article is a literature review that aims to find out how important the application is through finger painting in developing the fine motor skills of children who use their fingers and wrist movements in accordance with the Child Development Achievement Standards (STPPA) contained in the Regulation Minister of Education and Culture (PERMENDIKBUD) Number 137 of 2014 concerning National Standards for Early Childhood Education. Fine motor skills in this game will involve the development of small muscles, especially in the child's hand. Therefore the application of the finger painting game is expected to be suitable in achieving the fine motor development of children and this game does not deviate from the nature of the child namely learning through play which will indirectly develop the fine motor skills of the child contained in the STPPA related to hand movements namely coordinating the hands and eyes to make complicated movements, manipulative movements to produce a form with various media, and express themselves by creating art using various media.Kata kunci: finger painting, motorik halus, anak usia dini